Water and lipid migration in salted duck eggs during storage with different packaging conditions as studied using LF‐NMR and MRI techniques. Issue 5 (11th April 2022) - Dong, Xue; Zhang, Tan; Cheng, Shasha; He, Xiu; Wang, Haitao; Tan, Mingqian
Abstract : Abstract: Herein, the water and lipid migration of salted duck eggs during storage were systematically explored in three different packaging conditions of long‐term salting, no packaging, and vacuum packaging. Bound water, multilayer bound water, lipid, and bulk water were observed in the whole duck egg by low‐field nuclear magnetic resonance (LF‐NMR) relaxation. Five weeks of salting process led to the redistribution of water and lipid due to the watery state of egg white and the gelation of egg yolk due to the permeation of salt, and boiling mainly caused an obvious decrease in the mobility of bulk water due to the gelation of egg white. Among these three conditions, long‐term salting with 6 months storage caused the most serious redistribution of water and lipid as well as the rupture of the vitelline membrane, but could prevent the oxidation of egg yolk. Vacuum packaging had the least influence on the water and lipid distribution, mass change, and water content but led to lipid oxidation with high degree in egg yolk. However, the most obvious mass loss was observed in the salted duck eggs during the storage without packaging. In addition, principal component analysis of Carr–Purcell–Meiboom–Gill data suggested that LF‐NMR could distinguish the salted duck eggs with different storage times during the early stage of the storage. Practical Application: Water and lipid migration of salted duck eggs during storage with three packaging conditions were explored by using low‐field nuclear magnetic resonance and magnetic resonance imaging. Understanding the impacts of packaging conditions on water and lipid migration of salted duck eggs during storage could provide a new method for the quality identification.